Selective thermal transformation of value added cobalt from spent lithium-ion batteries. (15th April 2021) - Hossain, Rumana; Kumar, Uttam; Sahajwalla, Veena
Abstract: The significant usage of lithium-ion batteries (LIBs) in compact electronics – and more recently, electric automobiles – will lead to large quantities of scrap batteries and create serious environmental problems. Currently, spent LIBs are not very well recycled, and are predominantly disposed of in landfill. This is risky, due to the presence of hazardous materials in LIBs. However, LIBs contain numerous metallic resources such as copper, aluminium, cobalt and lithium. In particular, recovery of the transition metal cobalt is an attractive proposition as there is a scarcity in the supply of naturally mined cobalt, and there are economical and environmental issues associated with cobalt's mining processes. In this work, a facile process involving thermal disengagement and selective thermal transformation technique was employed for the recovery of valuable Co metal from spent LIBs. LiCoO2 and graphite were thermally disengaged from the cathode and anode of LIBs, and a further selective thermal transformation was carried out. This approach recovered ∼99% pure Cu and Al foils in the first step – using a thermal disengagement technique without any metal loss. Approximately 96% pure Co metal was recovered in the second step, using thermal transformation to enable carbothermal reduction and transformation at 1400 °C. This technology provides a guide for the successful recovery of valuable metal resources and future opportunities for the repurposing of valuable metals from LIBs.